Remedy Experience of Women Having Lost Their Family Members through Violence in Thailand’s Three Southernmost Provinces - Songwathana, Praneed; Baltip, Kansunaphat; Prompet, wattana; Wichaidit, Sujira (Journal of Thailand Nursing and Midwifery Council, 2018)
Abstract Objective: To study the remedy experience of women who had lost their family members through violence in Thailand’s three southernmost provinces, in a Thai BuddhistMuslim social context. Design: Qualitative research. Methodology: The respondents were 27 women who had lost their family members through violence in Thailand’s three southernmost provinces. Data were collected from January to August 2017, through semi-structured interviews, group discussions and nonparticipatory observation. The method of content analysis was employed for data analysis and result translation. Results: The respondents’ remedy experience involved two survival elements: 1) self-empowerment; and 2) external support. Self-empowerment involved fve methods: i) strengthening willpower; (ii) treating children as a moral stronghold; (iii) putting religious precepts into practice; (iv) thinking positively; and (v) making merits and committing good deeds. External support was found to be in four forms: (i) allowances to which they were entitled; (ii) career assistance; (iii) scholarships; and (iv) psychological remedy. Recommendations: This study could be used as a caregiving guideline. The fndings can be applied by caregivers and related staff to providing support, remedy and assistance for people affected by the violence in Thailand’s three southernmost provinces, to enable the victims to cope effciently with their losses and increase their physical and psychological strength. This study could also be applied to the process of using external help to empower the victims to continue living in a self-reliant, sustainable and more balanced manner.